2015
DOI: 10.1021/acs.langmuir.5b00625
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Tension Does Not Drive Asymmetric Nanoscale Electrowetting on Graphene

Abstract: We report molecular dynamics simulations of the electrowetting behavior of liquids in confinement between two oppositely charged graphene sheets. We observe that changes in the static contact angles of water, salty (4 M NaCl) water, and 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim][BF4]) (a room temperature ionic liquid) exhibit an asymmetric dependence on electric field polarity. The solid-liquid interfacial tension, which is expected to drive these changes, has been calculated independently by integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 52 publications
(126 reference statements)
0
29
1
Order By: Relevance
“…Our experimental results can also be compared to MD simulations done by Taherian et al They used a slightly different experimental setup where a nanodroplet of water was squeezed between a positively charged and a negatively charged graphene surface. In their study, asymmetric nanoscale electrowetting was observed.…”
Section: Discussionmentioning
confidence: 88%
“…Our experimental results can also be compared to MD simulations done by Taherian et al They used a slightly different experimental setup where a nanodroplet of water was squeezed between a positively charged and a negatively charged graphene surface. In their study, asymmetric nanoscale electrowetting was observed.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the sub-linear trend observed at higher voltages and humidity cannot be captured by the electromechanical model and cannot be explained by dielectric breakdown based on our current measurements (see the Supporting Information). It remains an important question to explore the shape of liquid nanocapillary bridges between conducting and dielectric surfaces subject to an applied electric field. …”
Section: Resultsmentioning
confidence: 99%
“…3 Electrowetting describes the influence of an electric field on wetting, and has been the subject of many fundamental studies. 4,5,6,7 Applications include electronic displays, 8 optical lenses 9 and lab-on-a-chip systems. 10 Electrowetting can be used to electronically control small amounts of liquid, without the mechanical movement of components, which is of paramount importance in microfluidic devices, 4,11 and considerable attention derives from this particular application.…”
Section: Introductionmentioning
confidence: 99%